HUBUNGAN TINGKAT STRES DENGAN SIKLUS MENSTRUASI PADA REMAJA PUTRI DI KELURAHAN DEMANGAN BANGKALAN - LELLY APRILIA VIDAYATI; Alis Nur Diana (NHM PRESS, 2023)
The menstrual cycle is the time from the first day of menstruation until the arrival of the next menstrual period. The menstrual cycle in women normally ranges from 21-35 days . Many teenagers experience stress so that their menstrual cycle is abnormal. The purpose of this study was to analyze the relationship between stress levels and menstrual cycles in young women in Demangan Bangkalan Village The research method used descriptive analytics with cross-sectional research design, respondents were 116 respondents. The independent variable is the stress level, while the dependent variable is the menstrual cycle using cross-tabulation and using the chi square statistical test. From the results of data analysis, it can be seen that most students experience irregular menstrual cycles, there are 63.8% and mild stress as much as 35.3%. After a statistical test of chi square ρ < α (0.03<0.05) showed that there was a meaningful relationship between stress levels and the menstrual cycle The effort to overcome it is to overcome the stress itself through therapy carried out by experts. If stress can be overcome, the menstrual cycle can be normal. Actually, stress can be cured in the following ways: laugh, think positively, exercise, eat nutritious food and drink enough water, make a work plan, do not procrastinate on tasks, do not run away, face it and improve the ability to face and handle stress.